PERSEPI MANFAAT MICRO TEACHING TERHADAP PENINGKATAN KOMPETENSI GURU SEKOLAH DASAR DALAM ASPEK PEDAGOGIK DAN KEPRIBADIAN - Betaubun, Martha; Fitriani, Fitriani; Rokhmah, Desy Eva Laila; Manauhutu, Fety Y (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to analyze the perceived benefits of microteaching in increasing the competence of elementary school teachers in pedagogical and personality aspects (Study of Unmus-UNY PPG Students). This is a quantitative descriptive research. The subjects of this research were active students who took part in Micro Teaching lessons at PPG Unmus-UNY, students who had completed the Microteaching course and elementary school principals as well as elementary school teachers who were certified as Teachers in the city of Merauke, with a total of approximately 30 respondents. The sampling technique uses purposive random sampling. Primary data is processed using simple statistics. Data collection was carried out in the form of FGD activities and the data was collected using a questionnaire which distributed via Google Form. The instrument used to obtain research data was by filling out a questionnaire. The data analysis technique used in this research is quantitative analysis. The type of scale used to measure data is the Likert scale. The results of this research found that the benefits of Microteaching for PPG–Unmus students provide great benefits in increasing competence in pedagogical and personality aspects. Most students, 75%, stated that they agreed with the benefits they received, while 0% said they disagreed.